Phytochemical Screening Of Eight Traditionally Used Ethnomedicinal Plants From Akola District (Ms) India - DIPAK KOCHE; RUPALI SHIRSAT; SYED IMRAN; D. G. BHADANGE (International Journal of Pharma and Bio Sciences, 2010)
The preliminary phytochemical analysis of eight ethnomedicinal plants from Akola District (MS) was done. The plants were Ocimum sanctum L., Hyptis suaveolens (L) Poit., Croton tiglium L., Physalis minima L., Tephrosia villosa (L) Pers., Malachra capitata L., Cleome viscosa L., and Galphimia glauca Cav. Qualitative phytochemical analysis of these plants confirms the presence of various phytochemicals like alkaloids, flavonoids, tannins, phlobatannin, terpenoid, saponin, steroid and cardiac glycosides in their aqueous leaf extracts. Some of these phytochemicals were further estimated quantitatively. Present paper deals with the significance of these phytochemicals with respect to the role of these plants in traditional medicinal system.